Narratology from the Seventies to the 21st Century - Cuvardic García, Dorde (2015)
This article explains the contributions published and shared since 1975 about the narrator, in the field of narratology. Mister Enrique Margery published, in the first issue of the Revista de Filología y Lingüística (May 1, 1975) his article “Thoughts on the Issue of the Narrator”, where he explained the narratology’s interpretation so far on the figure of the narrator in the 20th Century. Since then, proposals both complementary and alternative have appeared –or circulated among the Spanish and Latin American critics. These alternative proposals are at the core of this article: Norman Friedman’s proposal, Gérard Genette’s systematization, Bakhtin’s polyphony, the several modalities of paradoxical narration, the role and status of the narrator in the film discourse and the viewer’s participation in the building of the narrative act and in the forming of a semantically-coherent narration.